2013
DOI: 10.26719/2013.19.supp3.s76
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of congenital eye anomalies in a paediatric clinic in Ghana

Abstract: There is little information about the epidemiology of congenital eye anomalies in Ghana. We retrospectively reviewed the clinical records of 485 admissions to the paediatric eye centre of the Korle-Bu Teaching Hospital, Ghana (2004-2009 and 263 were diagnosed with at least one anomaly. Visual acuity was quantitatively assessed in 209 patients and 130 had some visual impairment; 49 with bilateral and 64 with unilateral blindness. The most frequent congenital anomaly overall was cataract (n = 44). In infants, c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
5
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 7 publications
4
5
1
Order By: Relevance
“…Sex distribution was found to be higher in males and prevalence of congenital ocular anomaly was higher within 4 years of age which is comparable with other study. 3,6,7 Most common disorder in our study is congenital cataract followed by uveal coloboma than whole globe anomaly like microphthalmos and anophthalomos, which is similar to the other studies. 3,6,7 Our study showed majority of congenital cataract were in the first birth rank and rest of anomaly like microphthalmos, anophthalomos, uveal coloboma and congenital glaucoma are more common in second birth rank, which is similar to another study done by Dutta and Bhattacharjee where incidence of congenital cataract is highest in second birth rank Incidence of colobomatous defect of the globe is highest in second birth rank (27%); next frequencies in third (20.43%) and then in fourth birth order (17.51%).…”
Section: Discussionsupporting
confidence: 91%
“…Sex distribution was found to be higher in males and prevalence of congenital ocular anomaly was higher within 4 years of age which is comparable with other study. 3,6,7 Most common disorder in our study is congenital cataract followed by uveal coloboma than whole globe anomaly like microphthalmos and anophthalomos, which is similar to the other studies. 3,6,7 Our study showed majority of congenital cataract were in the first birth rank and rest of anomaly like microphthalmos, anophthalomos, uveal coloboma and congenital glaucoma are more common in second birth rank, which is similar to another study done by Dutta and Bhattacharjee where incidence of congenital cataract is highest in second birth rank Incidence of colobomatous defect of the globe is highest in second birth rank (27%); next frequencies in third (20.43%) and then in fourth birth order (17.51%).…”
Section: Discussionsupporting
confidence: 91%
“…esotropia 11.1%/ and Ptosis 5.7%. 19 Out of 2254 children (0-5 years) examined at ophthalmology unit at Yaounde Gynae and Pediatric hospital (From Jan 2003 to Dec.2009), 150 presented eye anomalies. The most common anomalies were congenital lacrimal duct obstruction (66.66%), congenital cataract (10.9%) congenital glaucoma (10.9%) and congenital ptosis (3.77%).…”
Section: Resultsmentioning
confidence: 99%
“…[5][6][7][8][9][10][11][12] Eballe et al [13] reported a prevalence of 6.65% among children aged 0-5 years in Cameroun while Kaimbo Wa Kaimbo et al [14] reported a prevalence of 2.2% in Zaire. Furthermore, Ilechie et al [8] reported a markedly high prevalence 54% in a Ghanaian Paediatric Eye Centre that receives referral from the whole country while Bermejo and Martinez-Friaz reported a prevalence of 3.68/10000 newborns in an analysis of consecutive births in Spain [9]. In the light of the foregoing, the prevalence of COA varies from country to country and from region to region within the same country.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, COA was slightly more prevalent among males. Many authors had reported the predominance of COA among males [2][3][4][5][6][7][8]12]. On the contrary, Adekoya et al [11] reported COA predominance among the females studied.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation